Hair follicle stem cells promote epidermal regeneration under expanded condition - Zhang, Yu; Cui, Jiangbo; Cang, Zhengqiang; Pei, Jiaomiao; Zhang, Xi; Song, Baoqiang; Fan, Xing; Ma, Xianjie; Li, Yang (Frontiers in Physiology, 2024)
Skin soft tissue expansion is the process of obtaining excess skin mixed with skin development, wound healing, and mechanical stretching. Previous studies have reported that tissue expansion significantly induces epidermal proliferation throughout the skin. However, the mechanisms underlying epidermal regeneration during skin soft tissue expansion are yet to be clarified. Hair follicle stem cells (HFSCs) have been recognized as a promising approach for epidermal regeneration. This study examines HFSC-related epidermal regeneration mechanisms under expanded condition and proposes a potential method for its cellular and molecular regulation.